(untitled) (LINGUISTICA, 2015)
The study deals with those oppressions faced by Black American in œ12 Years a Slave movie and what resistances they showed toward those oppressions. The objectives of the study are to describe the oppressions faced by the two main characters “ Platt and Patsey and to explain the resistances they shown in œ12 Years a Slave Movie. This research focuses the study merely on oppression faced by two main characters; they were Salomon Northup or Platt and Patsey. This research was conducted by using descriptive qualitative design and limited on two of main characters. The data analysis result was found five kinds of oppression faced by black American in this film, those were: powerlessness, exploitation, marginalization, culture imperialism and violence. The resistances shown by American toward those oppressions were revolt, radicalism, asking for help and religion or spirituality. The issue of racism with oppression had been the crucial issue since long time ago which could not be denied that until nowadays the issue of racism is still happening though without oppression. The stigma of Black was being inferior and white was being superior had driven mind into the destruction of race relationship between Black and White. However, in this film we could see how badly the oppression faced by black American and how they struggled for fighting toward those oppressions.